2017
DOI: 10.1002/mnfr.201600731
|View full text |Cite
|
Sign up to set email alerts
|

A 12‐week intervention with nonivamide, a TRPV1 agonist, prevents a dietary‐induced body fat gain and increases peripheral serotonin in moderately overweight subjects

Abstract: A daily intake of 0.15 mg nonivamide helps to support to maintain a healthy body composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 43 publications
1
36
0
4
Order By: Relevance
“…In addition to a reduction of the subjective feeling of hunger and energy intake, plasma serotonin levels in this study were also increased after WPH + ARG intervention. We previously demonstrated that administration of 0.15 mg nonivamide increased plasma serotonin levels after a bolus dose, as well as after a daily dose in a 12 week human intervention study . In the present study, we demonstrate plasma serotonin levels to further increase after administration of a combination of 0.15 mg nonivamide with either 3.2 g l ‐arginine and/or 2 g wheat protein hydrolysate.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In addition to a reduction of the subjective feeling of hunger and energy intake, plasma serotonin levels in this study were also increased after WPH + ARG intervention. We previously demonstrated that administration of 0.15 mg nonivamide increased plasma serotonin levels after a bolus dose, as well as after a daily dose in a 12 week human intervention study . In the present study, we demonstrate plasma serotonin levels to further increase after administration of a combination of 0.15 mg nonivamide with either 3.2 g l ‐arginine and/or 2 g wheat protein hydrolysate.…”
Section: Discussionsupporting
confidence: 70%
“…Studies from our own group demonstrated a reduced energy intake and accompanied by increased plasma serotonin levels after a 0.15 mg bolus administration of nonivamide in a cross‐over human intervention trial . Furthermore, administration of a milk shake fortified with 0.15 mg nonivamide for 12 weeks to overweight, but otherwise healthy subjects, increased peripheral serotonin levels and prevented a dietary‐induced body fat gain . Also, on the cellular level, nonivamide has been shown to promote serotonin secretion by neural SH‐SY5Y cells …”
Section: Introductionmentioning
confidence: 92%
“…Apart from assessing the potential impact on satiation, which determines the size of a meal, participants were asked to document their diet using provided forms by estimating their food intake on both study days for 24 h post‐intervention to evaluate an influence on satiety, describing the inter‐meal period following the end of an eating episode . Analysis of the diet records was achieved by means of the software program nut.s (dato Denkwerkzeuge, nut.s science, v1.29.34; Austria) as described by Hochkogler et al …”
Section: Methodsmentioning
confidence: 99%
“…In our HFD rats, all treatments significantly improved glucose tolerance and IR, especially the combination therapy, which had a significantly higher effect. Salunkhe et al (Salunkhe et al, 2016) found that RSV improved insulin sensitivity by decreasing the compensatory insulin secretion and increasing glucose uptake, whereas PAVA improved insulin sensitivity due to its anti-obesity and antioxidant properties (Hochkogler et al, 2017;Morales-Martínez et al, 2016;Srinivasan, 2016).…”
Section: Rsv (3-hydroxy-3-methylglutaryl Coenzyme-a [Hmg-coa]mentioning
confidence: 99%
“…Administration of both PAVA and RSV resulted in improvement in metabolic parameters, endothelial function, and reduced oxidative stress in HFD rats. The activation of TRPV1 by PAVA has been reported to be associated with antiinflammatory, antioxidant, and anti-obesity effects (Srinivasan, 2016;Morales-Martínez et al, 2016;Hochkogler et al, 2017). RSV has been shown to have anti-inflammatory and antioxidant effects and to improve endothelial function (Deng et al, 2015;Nade et al, 2015;Schäfer et al, 2007;Suh et al, 2010).…”
Section: Rsv (3-hydroxy-3-methylglutaryl Coenzyme-a [Hmg-coa]mentioning
confidence: 99%